Lenalidomide enhances myeloma-specific T-cell responses in vivo and in vitro. (3rd May 2016) - Krämer, Isabelle; Engelhardt, Melanie; Fichtner, Sabrina; Neuber, Brigitte; Medenhoff, Sergej; Bertsch, Uta; Hillengass, Jens; Raab, Marc-Steffen; Hose, Dirk; Ho, Anthony D.; Goldschmidt, Hartmut; Hundemer, Michael
ABSTRACT: Immunomodulation is an important part of lenalidomide's mode of action. We analyzed the impact of lenalidomide on T cells from patients with multiple myeloma during lenalidomide therapy in vivo and in patients with lenalidomide-refractory disease in vitro Patients enrolled in the German Speaking Myeloma Multicenter Group (GMMG) MM5 trial received a consolidation therapy with two cycles of lenalidomide after autologous stem cell transplantation (ASCT). Half of the study population continued treatment with lenalidomide maintenance therapy for 2 y, while the other patients received lenalidomide maintenance therapy until complete remission. We analyzed 58 patients with (n = 30) or without (n = 28) lenalidomide therapy and 12 patients refractory to lenalidomide with regards to their anti-myeloma-specific T-cell responses displayed by IFNγ, Granzyme B, and Perforin secretion. The immunophenotype of T-cells was investigated by flow cytometry. Significantly, more myeloma-specific T-cell responses were observed in patients during lenalidomide therapy, compared to patients without treatment. Furthermore, we found on T-cells from patients treated with lenalidomide a decreased CD45RA expression, indicating a maturated immunophenotype and a decreased expression of CD57, indicating functional T cells. An improved myeloma-specific T-cell response was observed in 6 out of 12 heavily pretreated patients (refractory to lenalidomide) after in vitro incubation with lenalidomide. Complementary to the results in vivo, lenalidomide decreased CD45RA expression on T cells in vitro .